2023
DOI: 10.3390/d15040566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus cereus on Survival, Fecundity, and Host Adaptability of Pine Wood Nematode

Abstract: To clarify the role of bacteria in PWD, three PWNs with different virulence (strongly virulent strain AMA3, normally virulent strain AA3, and weakly virulent strain YW4) were selected as research objects, and three strains of Bacillus cereus (nematode-associated bacteria GD1, Pinus massoniana endophytic bacteria GD2, and P. elliottii endophytic bacteria NJSZ-13) at different concentrations were used to determine their effects on the survival and fecundity of the nematodes. The results showed that strains GD1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…against pine wood nematodes, suggesting their potential as agents for inducing plant resistance through the modulation of plant hormones [40]. Yuan et al found that Bacillus cereus could not only affect the survival and fecundity of pine nematodes but also reduce the extent of pine nematode infestation in Sargasso pine [41].…”
Section: Discussionmentioning
confidence: 99%
“…against pine wood nematodes, suggesting their potential as agents for inducing plant resistance through the modulation of plant hormones [40]. Yuan et al found that Bacillus cereus could not only affect the survival and fecundity of pine nematodes but also reduce the extent of pine nematode infestation in Sargasso pine [41].…”
Section: Discussionmentioning
confidence: 99%